PEMANFAATAN LEMBAGA PERJANJIAN PERIKATAN JUAL BELI DALAM PRAKTIK PEMBUATAN AKTA NOTARIS DI KABUPATEN MAGELANG - , MUHAMMAD NIZAM FANANI, Dr. Sutanto, SH, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to determine factors that cause the making of buying commitment in presence of notary before signing the Deed of Land selling transactions in Magelang district and also to determine the judicial power of the deed. This study is an empirical juridical study to figure out the reality that occurs in society, and analyzing the problem by comparing the normative values in legislation toward the reality. Type of data in this study is secondary and primary data. Secondary data include primary legal materials and the secondary legal materials are obtained from libraries, Internet sites, journals and magazines, while primary data obtained through interviews with respondents who meet the criteria set by the researchers, among others, who never made a deed of Notary, Notariesâ clients, officials and staff of Magelang District Land Office. It used a qualitative data analysis. From the study results, it concluded there are two factors that driving to make the buying commitment. one of the factors is the will of the parties in making the deed itself that is the payment of not fully given, the sold object have no any certificate, and external factors outside of both parties, that is Buying and selling some land, the buyer subjects exposed to the rules of the Land reform, burdened Mortgage Certificates, the land tax has not been raised SPPT on the ground objects. Both buying commitment Agency and selling deed have a legal force and provide legal protection to both sides but from a different angle.